Contempt of Court in Indonesia: A Legal Analysis Based on the Criminal Code and Islamic Law Principles - Malaka, Zuman (UNISSULA, 2025)
Contempt of Court involves actions that undermine the judiciary’s authority and disrupt the judicial process, posing a significant challenge to maintaining a just legal system. This study examines the concept of Contempt of Court in Indonesian positive law and Islamic law, analyzing relevant cases to highlight legal gaps. The research employs a normative legal method with statutory and conceptual approaches, analyzing secondary data from legislation, the Qur’an, Hadith, and scholarly literature. Findings reveal that Indonesian regulations on Contempt of Court are scattered across the Criminal Code, Narcotics Law, and Corruption Crime Law, lacking a unified framework, which leads to inconsistent enforcement, as evidenced by cases like courtroom disruptions and violence against judges. Islamic law principles, emphasizing justice and obedience to judicial authority, condemn such acts but are underexplored in Indonesia’s legal system. The study concludes that a dedicated Contempt of Court law, integrating positive and Islamic legal principles, is essential to ensure legal certainty, deter violations, and uphold a just and dignified judicial system. This research underscores the need for comprehensive regulations to strengthen judicial authority in Indonesia.